Health Care Convergence Analysis in Turkey on the Province Level: Spatial Quantile Method - Zeren, Fatma; Ozcan, Burcu; Mentese, Emin Yahya (Elsevier Science Bv, 2016)
The purpose of this study is to investigate the imparity of health care service in Turkey on the province level. Generally, beta convergence hypothesis is used for determining whether imparities are lowered. beta-convergence refers to an inverse relation between the relative growth rate of macroeconomic variable and its initial level. As a proxy variable for health care service, the number of practicing physicians per 10,000 individuals is used. The convergence hypothesis for health care service during the period from 2002 until 2010 is investigated by using the spatial quantile method. The results confirmed that there is convergence on province-basis for the period studied. In other words, it can be concluded that the imparity in terms of health care services offered to people in Turkey has decreased on the province level. There is also spatial interaction between provinces in terms of health care services. (C) 2016 Published by Elsevier B.V.
5th Istanbul Conference of Economics and Finance -- JUN 06-07, 2016 -- Yildiz Tech Univ, Istanbul, TURKEY
Keywords: Health care services; convergence; spatial dependence; province level; spatial quantile approach